2004
DOI: 10.1111/j.1365-2141.2004.05242.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils secrete MIP‐1β after adhesion to laminin contained in basement membrane of blood vessels

Abstract: SummaryWe have recently demonstrated that granulocyte colony‐stimulating factor (G‐CSF) stimulated the production of epithelial‐cell‐derived‐neutrophil attractant‐78 (ENA‐78) by neutrophils and that ENA‐78 might promote the accumulation of neutrophils that had migrated from the intravascular space into inflammatory tissues. In this study, we examined whether other chemokines could be secreted by neutrophils that had accumulated after migrating from the intravascular space into the inflammatory tissues. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Freshly-isolated neonatal and adult neutrophils stimulated with LPS had marked secretion of MIP-1 ␤ /CCL4, a chemokine involved in the recruitment of monocytes and neutrophils to inflammatory sites [43,46] , and is an observation consistent with existing literature [47,48] . We also now report that surviving neonatal neutrophils could be induced to secrete MIP-1 ␤ .…”
Section: Discussionsupporting
confidence: 73%
“…Freshly-isolated neonatal and adult neutrophils stimulated with LPS had marked secretion of MIP-1 ␤ /CCL4, a chemokine involved in the recruitment of monocytes and neutrophils to inflammatory sites [43,46] , and is an observation consistent with existing literature [47,48] . We also now report that surviving neonatal neutrophils could be induced to secrete MIP-1 ␤ .…”
Section: Discussionsupporting
confidence: 73%
“…Other neutrophil-derived chemokines such as MIP-1 , however, act on macrophages, T-cells and dendritic cells [25], and are considered to play a role in the regulation of immune responses [5]. Assessment of the MIP-1 content in PMN supernatants revealed that exposure to 10 ng/ml of MALP-2 induced the release of high amounts of MIP-1 in cultures of neutrophil granulocytes (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…GRO can also stimulate the production of O 2 − by neutrophils [22], which would also explain the increased production of O 2 − by neutrophils after the intense exercise. MCP-1 can be secreted by activated neutrophils [4,35,36,40]. No previous studies have been made on the effect of acute exercise on MCP-1 levels in healthy sedentary women.…”
Section: Discussionmentioning
confidence: 97%